HUBUNGAN FUNGSI AFEKTIF DAN STRATEGI KOPING DENGAN KENAKALAN REMAJA DI SMA NEGERI 107 JAKARTA - Refany Salsabila (2021)
The phenomenon of juvenile delinquency is always increasing. Juvenile delinquency is a problem that is not resolved properly due to one of the family functions, namely the ineffective affective function and the wrong use of coping strategies when adolescents experience a depressed situation. This study aims to determine whether there is a relationship between affective functions and coping strategies with juvenile delinquency. This study uses the Chi Square test with a cross sectional analytical survey approach. The population of this study were students of class 10 science, 11 social studies, and 12 science at SMA Negeri 107 Jakarta with a specified sample of 196 respondents using a sampling technique with cluster sampling. Collecting data using a questionnaire. The results showed that the affective function value (p value = 0.000) there was a relationship between affective function and juvenile delinquency and the value of coping strategies (p value = 0.001), which means that there was a relationship between coping strategies and juvenile delinquency. It is suggested that adolescents can avoid deviant behavior and use effective coping strategies to avoid juvenile delinquency and the formation of good affective functions Keywords: Affective Function, Coping Strategy, Juvenile, Juvenile Delinquency